2009
DOI: 10.1016/j.atherosclerosis.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mitochondrial cholesterol delivery protein, StAR, decreases intracellular lipids and inflammatory factors secretion in macrophages

Abstract: Hyperlipidemia is one of the most important risk factors for atherosclerosis. This can be amplified by a localized inflammatory response mediated by macrophages. Macrophages are capable of taking up excess cholesterol, and it is well known that delivery of cholesterol to the mitochondria by steroidogenic acute regulatory (StAR) protein is the rate-limiting step for cholesterol degradation in the liver. It has also been shown that overexpression of StAR in hepatocytes dramatically increases the amount of regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…ABCG1, as well as ABCA1, plays a vital role on HDL-dependent cholesterol efflux in rat aortic ECs (Lin et al, 2009). In the present study, we have shown that StAR overexpression can increase the mRNA and protein expression levels of ABCA1 and ABCG1 in microvascular ECs, bEnd.3 cells, indicating that StAR plays an essential role in the maintenance of cholesterol homeostasis in ECs, as well as in hepatocytes and macrophages, as previously reported (Hall et al, 2005;Ning et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…ABCG1, as well as ABCA1, plays a vital role on HDL-dependent cholesterol efflux in rat aortic ECs (Lin et al, 2009). In the present study, we have shown that StAR overexpression can increase the mRNA and protein expression levels of ABCA1 and ABCG1 in microvascular ECs, bEnd.3 cells, indicating that StAR plays an essential role in the maintenance of cholesterol homeostasis in ECs, as well as in hepatocytes and macrophages, as previously reported (Hall et al, 2005;Ning et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…bEnd.3 cells were transfected by recombinant adenovirus encoding StAR (Ad-CMV-StAR) at a multiplicity of infection (MOI)=10 plaque-forming units (PFUs)/cell for 48 h, as previously described (Ning et al, 2009). Cells infected by control adenovirus encoding enhanced green-fluorescence protein infections (Ad-CMV-EGFP) and cells without virus addition (Con.)…”
Section: Cell Infected By Adenovirus Encoding Starmentioning
confidence: 99%
See 2 more Smart Citations
“…STARD1 overexpression in human THP-1-derived macrophages also decreases total lipid and cholesterol levels (Bai et al 2009, Ning et al 2009a. The LXRa-dependent target genes ABCG1, PPARg, LXRa, and CYP27A1 are increased at the mRNA and protein levels in the STARD1 overexpressing cells.…”
Section: Stard1 and Oxysterol Production In Non-steroidogenic Tissuesmentioning
confidence: 85%